Primerjava merjenja bobnične, pazdušne in rektalne temperature pri novorojencih - Perčič, Simona (Medicinski razgledi, 2004)
Background: A tympanic membrane temperature measurements are in routine use also in neonates. Aim of our research was to evaluate the correlation between temperature measurements in the ear, axilla and in rectum of new-born infants.Methods: 27 term infants (1lgirls and 16 boys) who were hospitalised at the Neonatal Unit of the Paediatric Department in Ljubljana were included in study. All measurements of left and right ear, axilla and rectal temperature took place in incubator in thermally controlled environment. One hour after the first measurement the second measurement were repeated on the same places with the same instruments. Results: The differences of the temperature measurements between left and right ear were on average 0.4 °C (with standard deviation 0.3 °C). The differences of the temperature measurements in ear with one hour interval were on average 0.3 °C ( 0.2 °C), in axilla 0,06 °C ( 0,1 °C) and in rectum 0.09 °C ( 0.1 °C). 'fhe difference between simultaneous temperature measurements in ear and in the rectum were onaverage 0.4 °C ( 0,25 °C). The differences between under the same conditionsmeasured temperature at the axilla and rectum were on average 0,4 °C( 0,22 °C). Conclusion:Taking newborn's temperature from the ear or axilla is not very unpleasant for the infant, but the results of our and other published studies show that it could be unreliable in comparison with the rectal temperature measurement.
Keywords: Bobnič; Body Temperature; Methods; Pazduha; Rektum; Tympanic Membrane; Axilla; Telesna temperatura; Rectum; Novorojenček; Termometri; Thermometers; Infant, Newborn; merjenje; novorojenčki